Systemic histology of the marine water-strider halobates hayanus (Heteroptera, Gerridae) - Sinlapachai Senarat,; Naritsara Saeluea,; Ezra Mongkolchaichana,; Natthawut Charoenphon,; Wisut Sittichaya,; Narit Thaochan,; Pisit Poolprasert,; Anan Kenthao,; Korrawat Attasopa,; Piyakorn Boonyoung, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The structure and cell types of the organs of Halobates hayanus from Libong Island, Thailand, were investigated using a histological method. The integumentary system of this species consists of three layers: epicuticle, exocuticle, and endocuticle. Throughout the body, the muscular system exclusively included skeletal muscle. In the excretory system, we found four fully formed Malpighian tubules, each one lined with a straightforward cuboidal epithelium harbouring secretory granules. The digestive system comprised a foregut, midgut, and hindgut. The midgut had three distinct cell types: basal cells, epithelium, and absorptive cells. The nervous system comprised two regions: A ventral nerve cord and a frontal ganglion, which is connected to the eye structure. The frontal ganglion was composed of two lobes each containing an outer cortex and inner medulla. The outer cortex presented neurosecretory cells, neuroglia cells, and neurons. The neurosecretory cells were large and contained secretory granules in their cytoplasm. This histological study also showed the reproductive system of this gerrid species, including the reproductive tract, and the accessory organ.